WAKTU TUNGGU PENUMPANG BUS TRANS METRO BANDUNG - Rahmadiensyah, Raden Hudrian; Joewono, Tri Basuki (FSTPT Indonesia, 2015)
Waiting time is one factor that affects the quality of service of bus system. The longer the waiting time experienced by passengers, the lower level of satisfaction of Bus Rapid Transit passenger received. The purpose of this study is to analyze passenger waiting time and to analyze the effect of headway to the passenger waiting time distribution of Trans Metro Bandung bus route 2. Data analysis shows that the waiting time of passengers based on one week data fits with exponential distribution with an average value as much as 12.56 minutes. Analysis also shows that the waiting time of passengers at any headway group fit with Weibull distribution. Comparison of passenger waiting time among headway intervals have no significant difference.